Financial Knowledge and Millennials Investing Behaviors in Indonesia - Aang Kunaifi; Ahnan Naufal Fadlil Akbar (Institut Teknologi Sepuluh Nopember, 2019)
This research aims to investigate investment behavior in Indonesia millennialgeneration. Three variables are used to explain millennial behavior to havean investment account or unit. Consistent multivariate result found thatfinancial knowledge is positively associated with investment behavior. Theresults also found that personal factors such as age group and gender haverelationship on investment behavior. Junior age group and female havemorelikely to have an investment account or unit.